Difference of Maternal Serum Interleukin-8 in Preterm Labor and Full Term Labor - Budiartha, Komang W (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To determine the difference of maternal interleukin-8 (IL-8) in preterm labor and full term labor. Method: This is a cross sectional study with 68 samples, 29 subjects with preterm labor and 39 subjects with full term labor. IL-8 concentration was obtained from blood samples of the subjects, which were examined at Prodia Laboratory Denpasar. Data was analyzed using t-test for independent samples with =0.05. Result: The mean IL-8 level for the preterm labor group was 23.56 10.69 pg/ml and 12.19 5.79 pg/ml for the full term labor group. Statistical analysis using independent samples t-test showed that the average IL-8 level of both groups were significantly different (p=0.001). Conclusion: We concluded from this study that serum IL-8 concentration in women who had preterm labor is significantly higher in comparison to women who had full term labor. [Indones J Obstet Gynecol 2014; 4: 185-187] Keywords: full term labor, interleukin-8, preterm labor